Pengaruh Penghindaran Pajak pada Waktu Publikasi Laporan Keuangan dengan Struktur Kepemilikan sebagai Variabel Pemoderasi - Mulianingsih, Ni Luh Meina; Sukartha, I Made (E-Jurnal Akuntansi, 2018)
The aims of this study is to identify the effect of tax avoidance at the time of the publication on financial statements and the effect of institutional and managerial ownership as the moderator of the tax avoidance in the publication of financial statements. The sample was taken by purposive sampling method on the entire sectors of the registered firms in Indonesia Stock Exchange from 2014 until 2016. There are 106 firms with 3 years of observation; therefore the total of the observed sample is 318. The analysis technique used is logistic regression. The analysis result shows that the tax avoidance positively affects at the time of the publications of financial statements. Meanwhile, institutional and managerial ownership can weaken the positive effects of the tax avoidance at the time of the publications on financial statements. Keywords : Time of the publication on financial statements, tax avoidance, institutional ownership, managerial ownership.